2011
DOI: 10.1002/adma.201103190
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole Nanoparticles: A Potential Optical Coherence Tomography Contrast Agent for Cancer Imaging

Abstract: A near-infrared (NIR) absorbing contrast agent based on polypyrrole nanoparticles is described. Quantitative optical coherence tomography studies on tissue phantoms and Mie scattering calculations indicate their potential application for early-stage cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 41 publications
1
58
0
Order By: Relevance
“…[ 25 , 26 ] With strong NIR absorbance, PPy nanoparticles were used by Armes et al as a contrast agent for optical coherence tomography (OCT), signifi cantly improving OCT imaging sensitivity and facilitating the earlystage detection of cancers. [ 27 ] PPy nanomaterials have also been used in biosensors, drug delivery and nerve regeneration. [28][29][30][31][32][33] Although it has been reported that PPy can act as a thermal transducer of NIR radiation, [ 34 ] the potential use of PPy conductive polymers for photothermal treatment of cancer has, to the best of our knowledge, not yet been reported.…”
mentioning
confidence: 99%
“…[ 25 , 26 ] With strong NIR absorbance, PPy nanoparticles were used by Armes et al as a contrast agent for optical coherence tomography (OCT), signifi cantly improving OCT imaging sensitivity and facilitating the earlystage detection of cancers. [ 27 ] PPy nanomaterials have also been used in biosensors, drug delivery and nerve regeneration. [28][29][30][31][32][33] Although it has been reported that PPy can act as a thermal transducer of NIR radiation, [ 34 ] the potential use of PPy conductive polymers for photothermal treatment of cancer has, to the best of our knowledge, not yet been reported.…”
mentioning
confidence: 99%
“…These methods upgrade photothermal PPy nanocomposites to theranostic agents and enable the accumulation of concentrations in diseased areas sufficient to be visualized for both imaging and therapy purposes. In contrast to the MRI and ultrasound results, the intrinsic NIR absorption band of the PPy NPs enabled their use as a powerful biophotonics platform using the optical imaging modalities of optical coherence tomography 82 and PA technology 83 for tumor imaging. By exploiting NIR laser light and PPy optical contrast agents, a tissue treatment depth of~4.3 cm was achieved.…”
Section: Polymer Npsmentioning
confidence: 99%
“…Encouraged by the in vivo animal studies that low concentrations of PPy NPs (<200 μg mL −1 ) have very low long-term cytotoxicity26, PPy NPs have been demonstrated as an attractive OCT-absorbing (optical coherence tomography) contrast agent for tumor imaging27 and photothermal agent with high photothermal conversion efficiency for tumor ablation28 owing to the strong NIR absorption spectrum. Due to the truth that typical UCA is based upon microscale bubbles which are effective scatters of ultrasound waves29, it is highly desired to develop biocompatible NIR-absorbing PPy hollow microspheres (PPyHMs) with outstanding US-responsive capability for US imaging guided PTT.…”
mentioning
confidence: 99%